المجموعة الوقفية لمحمد العزيز الوزير في مكتبة الملك عبدالعزيز بالمدينة المنورة: دراسة وصفية تحليلية - المزيني، عبدالرحمن بن سليمان (مركز بحوث ودراسات المدينة المنورة, 2008)
This study presents the biography of Al-Sheikh Muhammad Al-Aziz Al-Wazeer and describes the collection of manuscripts which he possessed (5569 books). Some of them are handwritten, others printed according to the library index which is composed of 780 pages and another collection index of 78 pages. This collection comprises the subjects of the sciences of the Holy Quran and the sciences of its interpretation. It also deals with the Prophetic tradition and its sciences, the principles of jurisprudence, religious obligations, legal politics, rhetoric, literature, logic and indices. These are preserved in King Abdul Aziz Library in Al-Madinah Al-Munawwarah.
Keywords: الوقف -- المخطوطات العربية -- الوزير، محمد العزيز -- مكتبة الملك عبدالعزيز -- المدينة المنورة